Pengaruh Pengaruh Konten Guru Konten Kreator Terhadap Minat Mahasiswa PGSD UMP Menjadi Guru Sekolah Dasar - Ichwani, Kartika Isnayu; Yuwono, Pratik Hari (Jurnal Gentala Pendidikan Dasar, 2025)
The digital era has brought significant changes to the field of education, with technology playing a central role. One prominent impact is the rise of social media, which is now widely used by teachers to share teaching experiences and educational content. Platforms such as TikTok and Instagram have seen an increasing number of teachers, known as Teacher-Content Creators, who produce and share content related to the teaching profession. These educators share a variety of materials, including engaging learning resources, creative teaching media, content about teacher-student relationships, and ideas for icebreaker activities. Their presence on social media provides younger generations with insights into the teaching profession, including how to create a fun and effective learning environment. This exposure has the potential to inspire young people to pursue a career as elementary school teachers. This study aimed to determine whether the content shared by Teacher-Content Creators contributed a partial and simultaneous effect on the interest of students in the Primary School Teacher Education Program at Universitas Muhammadiyah Purwokerto in becoming elementary school teachers. Using a quantitative approach, the research findings revealed that, partially, the content had no significant effect. However, simultaneously, the content exerts a notable effect on the students interest in becoming elementary school teachers.